(untitled) (Jurnal Simki Economic, 2022)
This research was conducted to determine the effect of Local Revenue, General Allocation Funds, Special Allocation Funds, and Population Amounts on Capital Expenditures in the Special Province of Yogyakarta. Law No. 22 of 1999 concerning Regional Government is a juridical basis for regional economic development in Indonesia. The locations in this study are districts and cities in the Special Province of Yogyakarta. Capital expenditure is an output that greatly affects development. Because capital expenditure is a fixed asset and has long-term benefits, it makes capital expenditure a reference for improving development and increasing people’s purchasing power. Research data in the form of secondary data. The results of the study show that Regional Original Income and Population Influence on Capital Expenditures in the Special Province of Yogyakarta. While the General Allocation Fund and Special Allocation Funds have no effect on Capital Expenditures in the Special Province of Yogyakarta.